Fertilización orgánica y química en el desarrollo y producción de dos híbridos de pimiento (Capsicum annuum) en la zona de Puerto Quito - Vega Morales, Gabriel Miguel (2013)
The present investigation was carried out in canton Port I Remove county of the Pichincha, in the sector I Laugh Salazar, Area 18, property is Founded of the Guanábano, property of Mr. José Vega, km 163 via Calacalí the Independence, in the cultivation of the hybrid pepper "'Quetzal" ' "Salvador", with the purpose of studying its behavior agronomic field with a spaced of 50 X 50 centimeters; to identify the organic better fertilization class without taking into account the appropriate populational density to increase the yield of fruits; and, to carry out the economic analysis of the yield of fruits in function at the cost of the treatments. The payment classes Bovinaza, bovinaza humus, porquinaza, porquinaza humus and a chemical fertilizer were studied. The doses and times of application of the fertilizer were not considered; each dose was applied with an interval of 15 days after the transplante and beginning of the reproductive stage. The treatments were constituídos for the combination of the two factors. The experimental design of a factorial arrangement of 2X5, was used with a design "complete Blocks at random" in four repetitions. The experimental parcel was constituída for 2 arrays of 2m of longitude, separated to 0,50m, giving an area of 6m2 (3m x 2m). The useful area of the parcel was determined by the borders left with 0.50 centimeters of security. The variables were evaluated: days to the floración; plant height to the 15, 30,45 and 60 days. In the first crop longitude and diameter of the fruit were evaluated; fruits for plant; I weigh of the fruit and yield of fruits. The evaluated variables underwent the variancia analysis and to determine the statistical difference among the stockings of the populational densities the test it was used he/she Differs Minimum Significant (D.M.S.) and the test of Tukey to 95% of probability to determine the statistical difference between the stockings of dose of the fertilization and interaction of the two factors...........